Investigation of methane gas bubble dynamics and hydrate film growth during hydrate formation using 4-D time-lapse synchrotron X-ray computed tomography - Khan, Shadman H.; Sahoo, Sourav Kumar; Falcon-Suarez, Ismael Himar; Marin-Moreno, Hector; Sutiyoso, Hanif; Madhusudhan, B. N.; Majumder, C. B.; Arora, Amit; Best, Angus I. (Frontiers in Earth Science, 2024)
We present a time-lapse 4-D high-resolution synchrotron imaging study of the morphological evolution of methane gas bubbles and hydrate film growth on these bubbles. Methane gas and partially water-saturated sand were used to form hydrate with a maximum hydrate saturation of 60%. We investigated the transient evolution of gas bubble size distribution during hydrate formation and observed three distinct stages: a) nucleation and hydrate film formation, b) rapid bubble break-up, c) gas bubble coalescence and hydrate framework formation. Our results show that the average gas bubble size distribution decreases from 34.17µm (during hydrate nucleation) to 8.87 µm (during secondary bubble formation). The small-size methane bubble population (mean diameter below 10 µm) initially increases at the expense of the larger methane bubble population (mean diameter above 50 µm) due to breakage of the larger bubbles and coalescence of the smaller bubbles. We quantified that the average hydrate film thickness increases from 3.51µm to 14.7µm by tracking the evolution of a particular gas bubble. This thickness increase agrees with an analytical model with an average deviation error of 3.3%.This study provides insights into gas bubble distribution and hydrate film growth during hydrate formation, both of which impact the geophysical and mechanical properties of hydratebearing sediments.